Influence of dispersion gas flow on the spray characteristics and γ-Fe2O3 nanoparticles formation and properties in reference SpraySyn burners - Massopo, Orlando; Tischendorf, Ricardo; Gonchikzhapov, Munko; Kasper, Tina; Augustin, Peter; Özer, Burak; Reddemann, Manuel; Kneer, Reinhold; Sheikh, Mohammed-Ali; Mert, Aydan Akyildiz; Wiggers, Hartmut; Schmid, Hans-Joachim (Powder Technology)
This study investigates the effect of dispersion gas (DG) flow on the formation and properties of maghemite (γ-Fe2O3) nanoparticles using standardized SpraySyn burners (SS1 and SS2). Several diagnostics were employed to characterize the spray and nanoparticles. Increasing DG flow (6 - 12 slm) results in smaller droplet sizes (DS), cooler flame temperatures, shorter high-temperature droplet/particle residence times, and smaller agglomerates in the size range of 5 - 12 nm with narrower primary particle size distribution, corresponding to higher mass fractal dimensions, as supported by TEM and SMPS analysis, resulting in more compact agglomerates. BET and TEM confirmed decreasing primary particle sizes with increasing DG flow. Raman and XRD analyses predominantly identified maghemite, which shows a bimodal distribution of crystallite sizes, while SS1 samples have a greater proportion of larger crystallites. The self-preserving size distributions of agglomerates with a geometric standard deviation of 1.5 are reached faster with increasing DG flow. The barrier effect of DG observed in SS1 leads to slower droplet combustion kinetics, higher temperatures, and delayed precursor release, which, along with downstream flow recirculation, result in significantly higher agglomeration rates outside the visible flame. SS2 demonstrates improved atomization, more stable flames, and finer, uniform nanoparticles with less carbonaceous residues (CR). Conversely, SS1 showed broader DS distributions and higher CR levels on the γ-Fe2O3 surface, especially at higher DG flow. This work highlights the essential role of DG flow and nozzle geometry in controlling droplet evaporation, flame stability, and nanoparticle growth, offering insights for optimizing SFS and validating numerical models.
Keywords: Spray flame synthesis; iron oxide nanoparticle; SpraySyn burner; Dispersion gas; Coaxial atomization; HiaT-SMPS

Large eddy simulation of iron oxide formation in a laboratory spray flame (Applications in Energy and Combustion Science)
Iron oxide nanoparticles are very interesting for many applications in different industrial sectors. A promising process to manufacture these nanoparticles is flame spray pyrolysis (FSP). A lack of understanding of the individual sub-processes in FSP makes it challenging to tailor nanoparticle properties. This work provides insights into the formation of iron oxide nanoparticles in a turbulent spray flame using Large Eddy Simulations (LES), which are based on a comprehensive model, including customized submodels. Highlights are the adaption of a turbulent combustion model and a bivariate hybrid method of moments for modeling nanoparticle dynamics. The work focuses on the SpraySyn burner, which is a standardized laboratory burner and was operated with a precursor-solvent mixture of ethanol and iron(III) nitrate nonahydrate. For studying the relevance of precursor chemistry, LES using an evaporation-limited precursor chemistry model is compared with a model that includes detailed iron chemistry. A further novelty is the inclusion of adsorption in the simulation, which defines a third model for comparison. Sufficient validation is achieved for the undoped LES using experimental data from the literature. A strong impact of the detailed iron chemistry and adsorption is found on the precursor consumption and the aggregate and primary particle formation. Comparing the particle diameters with experimental measurements from the literature and data generated for this work is found unsuitable to asses the precursor chemistry model and revealed an urgent need for future experimental and numerical research. This work serves as a step forward in realizing a reliable model.
Keywords: Flame spray pyrolysis; Iron oxide formation; Large eddy simulation; Method of moments; SpraySyn

Thermal and chemical structure of ethanol and 2-ethylhexanoic acid/ethanol SpraySyn flames - Gonchikzhapov, Munko; Kasper, Tina (Applications in Energy and Combustion Science)
Keywords: Nanoparticle synthesis; Flame spray pyrolysis; SpraySyn burner; Flame structure; Species distribution; Temperature distribution

Einfluss der Zerstäubung auf diePartikelbildung bei der Sprayflammenpyrolyse (Vortrag) - Massopo, Orlando; Tischendorf, Ricardo; Schmid, Hans-Joachim; Fröde, Fabian; Pitsch, Heinz; Reddemann, Manuel; Grenga, Temistocle; Kneer, Reinhold
Keywords: SpraySyn; Flammenspraypyrolyse; Maghemite Nanopartikel; Gas to particle-Syntheseweg; Probennahme; Verunreinigung